Preparing Live Donor for Kidney Donation - Mahdavi, Reza (Urology Journal, 2009)
Purpose: In order to select the most appropriate donor and minimize psychological and physical complications in the kidney donors, it is of high importance to prepare the donor meticulously. The essential respective items are reviewed in this study. Materials and Methods: The available published literature and papers presented in Medline from 1983 to 2003 were reviewed. Results: One the sources of sources of kidney donation is the live donor which is mostly used in Iran. Similarly, due to long waiting lists of kidney recipients, live donor kidney transplantation have been increasingly used in developed countries. Consequently, several aspects of this issue have been considered and specific recommendations have been discussed; anatomy of the donor's kidney, age, ABO blood group, viral infections, weight, HLA type compatibility, psychological status, and diseases such as diabetes, ADPKD, and Alport syndrome should be evaluated in donation candidates. Conclusion: Live donor kidney donation has the advantage of elective and programmed transplantation over cadaveric transplantation. However, removal of an intact organ from the body of a normal individual may lead to complications, as it may so in any other major surgical operation. Thus, it is strongly recommended to select the most appropriate donor patiently by a series of accurate evaluations.